Gustavo Garza Villarreal, La gestión municipal en el Área Metropolitana de Monterrey 1989-1994, México, Miguel Ángel Porrúa/Instituto de Investigaciones Sociales, UNAM, 1998 - Cabrero Mendoza, Enrique (Estudios Demográficos y Urbanos, 1999)
Gustavo Garza Villarreal, La gestión municipal en el Área Metropolitana de Monterrey 1989-1994, México, Miguel Ángel Porrúa. Instituto de Investigaciones Sociales, UNAM, 1998.